CONTENTS (Medical Forum Monthly, 2024)
C-Reactive Protein and Total Leukocyte Count in the Diagnosis of Acute Appendicitis 2-5 Viqar Aslam 2. Shabab Hussain 3. Muhammad Sherose Khan 4. Sajjad Muhammad Khan 5. Raza UllahCompare the effectiveness of Prostaglandin E2 Vaginal Gel versus Vaginal Tablets for the induction of Labour at Term 6-8 Shahzadi Saima Hussain, 2. Syeda Sitwat Fatima 3. Qudsia Qazi 4. Tanveer ShafqatHistopathological Evaluation of Uterine Curettings in Patients with Abnormal Uterine Bleeding 9-12 Afsheen Qazi 2. Anila Faisal Memon 3. Ghulam Mustafa Yousfani 4. Amin Fahim 5. Aneela QureshiSerum Magnesium Levels in Migraineurs versus non Migraineurs 13-15 Jawwad us Salam 2. Munir Hussain Siddiqui 3. Akhtar Ali Baloch 4. Mohammad Aurangzeb 5. Sadaf Ahmed Asim 6. Mohammad MasroorPredicting Wellbeing in Irregular Shift Workers 16-19Surriya Jabeen 2. Aneesa Matloob 3. Ayesha SarwatHealth Care Service Quality: A Comparison of Public and Private Hospitals in Karachi 20-24 Zeba Saeed 2. Zainab Hassan 3. Syed Mohsin Turab 4. Syeda Amber Zaidi 5. Saira Kiran 6. Mehrukh Zehravi 7. Sehar ChudaryHealth Education for Enhancement of Self Efficacy of Young Females 25-28Sarah ShahedOcular Manisfestations in Xeroderma Pigmentosum; A series of 20 Patients 29-31 Irfan Shaikh 2. Partab Rai 3. Bahram Khan KhosoOutcome of Operative and Non Operative Treatment of Glenoid Fossa Fractures in a Tertiary Care Hospital in Peshawar 32-35 Mohammad Tariq Ijaz Afridi 2. Farooq Munfaet Ali Khan 3. Tanveer Sadiq Chaudhry 4. Viqar Afridi 5. Asnad Etiology and Epidemiology of Patients Presenting with Liver Disease During Pregnancy 36-39 Aftab Haider Alvi 2. Mirza Muhammad Ilyas Baig 3. Omer SabirPolydioxanone vs Prolene Closure for Midline Abdominal Incisions: To Compare Postoperative Wound Dehiscence 40-43 Afzal Siddique 2. Malik Asrar Ahmed 3. Zia-ur-RehmanRole of Malignancy Index in Prediction of Malignancy in Ovarian Masses Preoperatively 44-47 Nadeem Shahzad 2. Nawaz Rashid 3. Sadaf Zahra 4. Aisha MalikThe Analysis of Clinoepidemiological Variables of Psoriasis in a Tertiary Care Hospital in Karachi, Pakistan 48-51 Bahram Khan Khoso 2. Irfan Shaikh